2017
DOI: 10.1021/acs.langmuir.7b01339
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficiently Delaminated Single-Layered MXene Nanosheets with Large Lateral Size

Abstract: Single layered TiC(OH) nanosheets have been successfully fabricated by etching its TiAlC precursor with KOH in the presence of a small amount of water. The OH group replaced the Al layer within the TiAlC structure during etching, and TiC(OH) nanosheets could be easily and efficiently achieved through a simple washing process. The delaminated single-layered nanosheets are clearly revealed by atomic force microscopy to be several micrometers in lateral size. Interestingly, the exfoliated TiC(OH) nanosheets could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(122 citation statements)
references
References 31 publications
2
120
0
Order By: Relevance
“…Generation of -F surface groups, unwanted etching of the transition metal element (due to low selectivity toward A-layer atoms), and being environmentally unfriendly are the main problems of these synthesis processes. [16,57,[69][70][71] Moreover, it has been reported that AlF 3 , one of the byproducts of the etching reaction, when the A-layer atom is Al, is hard to be eliminated from the mixture under mild conditions. [69] Therefore, recently, many attempts to develop fluoride-free synthesis strategies have been reported.…”
Section: Synthesis Of Single-layer Mxene Flakesmentioning
confidence: 99%
“…Generation of -F surface groups, unwanted etching of the transition metal element (due to low selectivity toward A-layer atoms), and being environmentally unfriendly are the main problems of these synthesis processes. [16,57,[69][70][71] Moreover, it has been reported that AlF 3 , one of the byproducts of the etching reaction, when the A-layer atom is Al, is hard to be eliminated from the mixture under mild conditions. [69] Therefore, recently, many attempts to develop fluoride-free synthesis strategies have been reported.…”
Section: Synthesis Of Single-layer Mxene Flakesmentioning
confidence: 99%
“…15,[18][19][20][21][22] Besides these, etching by ammonium biuoride (NH 4 HF 2 ) and KOH has also been proposed. [23][24][25] Among these etchants, the HCl/LiF etchant has been found to be the most suitable alternative to the highly toxic HF acid, and it is also used to synthesize more conducting claylike MXenes. Aer etching, the MXene layers can be exfoliated further by sonication or by the metal ions-intercalation or guest molecules, 16,26,27 fabricating hybrid structures with graphene.…”
Section: Introductionmentioning
confidence: 99%
“…The diazonium salt solution was then added slowly to the intercalated MXene solution while stirring at 0–5 °C for about 4 h. Adding aryl groups to the negatively charged surfaces of MXenes can help weaken the cohesive bonding between the layers of the MXenes along the intercalating positive ions, which results in large‐scale multilayered flakes. Fluoride‐free fabrication of single‐layered Ti 3 C 2 flakes by etching the Ti 3 AlC 2 with KOH and water is also reported . The OH groups were able to take the place of Al in the MAX phase and by washing the solution with H 2 O to remove KAlO 2 by‐products, monolayered Ti 3 C 2 (OH) 2 nanosheets with the thickness of about 1.5 nm could be fabricated.…”
Section: Synthesis Of Mxenes: Etching and Delaminationmentioning
confidence: 94%